Review of Pharmacological Properties, Phytochemistry and Medicinal Uses of Baccharoides adoensis - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Baccharoides adoensis is a shrub widely used as traditional medicine throughout its distributional range in tropical Africa. This study is aimed at providing a critical review of the pharmacological properties, phytochemistry, and medicinal uses of B. adoensis. Documented information on the pharmacological properties, phytochemistry, and medicinal uses of B. adoensis was collected from several online sources which included Scopus, Google Scholar, PubMed and Science Direct. Additional information on the pharmacological properties, phytochemistry, and medicinal uses of B. adoensis was gathered from pre-electronic sources such as book chapters, books, journal articles, and scientific publications sourced from the university library. The articles published between 1962 and 2020 were used in this study. This study showed that the roots, flowers, stems, and leaves of B adoensis are widely used as ethnoveterinary medicine and traditional medicines for backbone pain, reproductive problems, kidney diseases, fever and febrile complaints, wounds, ulcers, sexually transmitted infections, skin complaints, malaria, gastro-intestinal problems and respiratory problems. Phytochemical compounds identified from the species include alkaloids, carbohydrates, chondrillasterol, flavonoids, free sugars, glaucolides, glycosides, phenols, proanthocyanidin, saponins, steroids, tannins and terpenoids. Pharmacological research revealed that B. adoensis extracts and compounds isolated from the species have antimicrobial, antimycobacterial, anti-inflammatory, antioxidant, antiplasmodial, anti-pyretic, antitrypanosomal, antileishmanial, anti-ulcer and gastroprotective, immunomodulating, inhibition of Helicobacter pylori adhesion, larvicidal, cytotoxicity and toxicity activities. Baccharoides adoensis should be subjected to detailed phytochemical, pharmacological, and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological activities.